The evaluation of nociceptive intensity by using free radicals direct measurement by EPR method in the tail of anaesthetized rats - Rokyta, Richard; Stopka, Pavel; Kafunkova, Eva; Krizova, Jana; Fricova, Jitka; Holecek, Václav (Neuro endocrinology letters, 2008)
OBJECTIVES: The aim of the study was to demonstrate the ability to measure free radicals and singlet oxygen, using EPR methods, in the tail of anaesthetized rats. The advantage of this method lies in the potential for continuous evaluation of free radicals and singlet oxygen during nociceptive processes. METHODS: Electron paramagnetic (spin) resonance (EPR/ESR) was used. DMPO and PBN as spin traps and thermal mechanical pulp (TMP) as a spin detector of singlet oxygen were used. Thirty-one adult male (Wistar) rats were used for the experiments. They were housed according to principles of good laboratory practice. The animals were stimulated for 10 minutes on 5 consecutive days by using clamps on the hind limbs. During the EPR measurement they were anaesthetized with a mixture of ketamine and xylazine. Hydroxyl and nitroxide free radicals, as well as singlet oxygen were measured. RESULTS: After nociceptive stimulation, free hydroxyl radicals were increased as well as free nitroxide radicals. Singlet oxygen was also increased after nociceptive stimulation. Antioxidants significantly decreased the increase in hydroxyl radicals after nociceptive stimulation. CONCLUSIONS: Our results confirmed an increase in free radicals and singlet oxygen after nociceptive stimulation and a reduced increase after application of antioxidants. Direct EPR methods were first used in the tail of anaesthetized rats and represent an extremely useful tool for the evaluation of pain intensity in living animals.
Keywords: Animals; Antioxidants; Pain Measurement; Pain Threshold; Rats, Wistar; Tail; oxidy dusíku; Free Radicals; hydroxylový radikál; Singlet Oxygen; měření bolesti; Electron Spin Resonance Spectroscopy; bolest; Male; antioxidancia; ocas; krysa rodu Rattus; Pain; elektronová paramagnetická rezonance; zvířata; mužské pohlaví; singletový kyslík; práh bolesti; Nitrogen Oxides; Rats; Hydroxyl Radical; volné radikály; potkani Wistar